(untitled) (Eurasian Journal of Philology Science and Education, 2019)
The etymology of plural suffixes in Turkish languages was researched by well-known scientists in foreign countries and the Soviet Union. But none of them did not make a common decision. For example, suffixes of the plural in Kazakh languages -lar/ler, -tar/-ter, -dar/der archetype of forms was -lar suffix. Results of last researchers showed that archetype is not -lar and -tar is known archetype. In general, on the basis of the laws of language development, it was established that meaning of plural is preserved only if there is t, d, s, z, sh, ch sound in the plural form. These sounds give plural meaning even in a system of languages. It seems that «ta» is used in «plural» meaning and «ar» is used «part» meaning. These discoveries should be considered in the future.